LITERATUR REVIEW: PENGARUH SCREEN TIME TERHADAP MASALAH PERILAKU ANAK - Simanjuntak, Susi (Universitas Sam Ratulangi, 2023)
Introduction: Technological developments and easy access to digital devices cause excessive screen time in children. Excessive screen time in children can cause various problems in children. This review aimed to examine the association between screen time and behavioral problems of children. Methods: Three databases were searched, including ScienceDirect, Medline/Pubmed, and Google Scholar databases. Articles were selected using inclusion criteria, namely articles that have been limited since the last five years (2019-2023), are pure research articles, full text, and in English. Results: Eight articles were included in this review. The research was conducted in 8 countries namely Spain, Korea, China, Saudi Arabia, Turkey, the United States, Canada, and Israel with an age range from 1-18 years. Research instruments used to measure behavioral problems in children vary. Conclusion: This review identified that there is a relationship between increased screen time and increased behavior problems in children. Keywords: behavior problem; children; screen time